2010
DOI: 10.1007/s10637-010-9554-8
|View full text |Cite
|
Sign up to set email alerts
|

Riccardin D, a novel macrocyclic bisbibenzyl, induces apoptosis of human leukemia cells by targeting DNA topoisomerase II

Abstract: We studied the effect of riccardin D, a macrocyclic bisbibenzyl, which was isolated from the Chinese liverwort plant, on human leukemia cells and the underlying molecular mechanism. Riccardin D had a significant antiproliferative effect on human leukemia cell lines HL-60, K562 and its multidrug resistant (MDR) counterpart K562/A02 cells, but showed no effect on the topoisomerase-II-deficient HL-60/MX2 cells, as measured by the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. The pBR322… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Topo II-mediated supercoiled pBR322 DNA relaxation assay DNA topo II activity was estimated by the supercoiled pBR322 DNA relaxation assay as described previously [9,24]. The .…”
Section: Nuclear Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Topo II-mediated supercoiled pBR322 DNA relaxation assay DNA topo II activity was estimated by the supercoiled pBR322 DNA relaxation assay as described previously [9,24]. The .…”
Section: Nuclear Extract Preparationmentioning
confidence: 99%
“…Riccardin D was found to have an anticancer activity on human leukemia cell lines HL-60, K562 and its MDR counterpart K562/A02. Riccardin D might induce leukemia cell apoptosis through the inhibition of DNA topo II [9]. Another study suggested that riccardin D might hold the activity of antiangiogenesis as demonstrated in human umbilical vein vascular endothelial cells (HUVEC) and lung carcinoma H460 xenografts in mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Riccardin D, isolated from a Chinese liverwort was found to possess pronounced antiproliferative effect on human leukemia cell lines HL-60, K562 and MDR K562/A02 cells. No induction of apoptosis in topoisomerase-II-deficient HL-60/MX2 cells indicates the mode of action of riccardin D is DNA topoisomerase-II dependent [132] .…”
Section: Bibenzyls and Bisbenzyls 2151 Riccardinmentioning
confidence: 98%
“…RNA quality was determined based on the ratio of A260/ A280 (1.8-2). The concentration of total RNA was measured by detecting absorbance at 260 nm (A260) (18). Then, reverse transcription (RT) was performed with 2 μg of extracted RNA using the First Strand cDNA Synthesis Kit (Toyobo, Osaka, Japan) according to the supplied protocol.…”
Section: Effects Of Akba On Sensitivity To Vcrmentioning
confidence: 99%